The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41598-017-02672-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Detection, and Quantification of Cancer Biomarkers in HPV-Associated Malignancies

Abstract: Human Papillomavirus (HPV) infection has been recognized as the main etiologic factor in the development of various cancers including penile, vulva, oropharyngeal and cervical cancers. In the development of cancer, persistent HPV infections induce E6 and E7 oncoproteins, which promote cell proliferation and carcinogenesis resulting elevated levels of host antibodies (e.g., anti-HPV16 E7 antibody). Currently, these cancers are clinically diagnosed using invasive biopsy-based tests, which are performed only in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…, exposure rate to high-risk HPV types), a variety of methods was developed for these purposes [35]. The studies showed that the anti-HPV16 E7 antibody could be used as a blood biomarker for HPV infections [4]. Moreover, antibodies against HPV virus-like particles (VLPs) were considered as a marker of HPV infection, and were associated with HPV-related disease, but not as strongly as E6 and E7 antibodies [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, exposure rate to high-risk HPV types), a variety of methods was developed for these purposes [35]. The studies showed that the anti-HPV16 E7 antibody could be used as a blood biomarker for HPV infections [4]. Moreover, antibodies against HPV virus-like particles (VLPs) were considered as a marker of HPV infection, and were associated with HPV-related disease, but not as strongly as E6 and E7 antibodies [36].…”
Section: Discussionmentioning
confidence: 99%
“…Among the high-risk HPVs, types 16 and 18 are responsible for the majority of cervical cancer in the world especially in Iran [1, 3]. The persistent HPV infections generate E6 and E7 oncoproteins which promote cell proliferation and carcinogenesis leading to increased levels of host antibodies [4]. As known, HPV DNA test along with routine Pap smear could reduce colposcopy rate in ASCUS patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic devices provide various advantages over conventional plate-based microwells for diagnostic tests such as blood separation and cell count. [40] Such advantages include, precise control of sample volume with minuscule amount, wide range of geometries mimicking the biological environment, and ability to expose the biological moieties to shear stress using flow thus mimicking their natural environment. [41,42]…”
Section: Discussionmentioning
confidence: 99%
“…They validated the nanosensor in serum samples and supplied high responses as compared with control samples. They showed that this nanosensor can be implemented as a pretesting tool to diagnose for broad monitoring of HPV-associated cancers [84]. Teengam et al reported a colorimetric nanosensor to screen synthetic HPV.…”
Section: Human Papillomavirusmentioning
confidence: 99%